Searching for a mitochondrial root to the decline in muscle function with ageing. Issue 3 (18th May 2018) - Gonzalez‐Freire, Marta; Adelnia, Fatemeh; Moaddel, Ruin; Ferrucci, Luigi
Abstract: Sarcopenia, the age‐related loss of muscle mass and strength, is linked to a range of adverse outcomes, such as impaired physical performance, cognitive function, and mortality. Preventing sarcopenia may reduce the burden of functional decline with aging and its impact on physiological and economic well‐being in older adults. Mitochondria in muscle cells lose their intrinsic efficiency and capacity to produce energy during aging, and it has been hypothesized that such a decline is the main driver of sarcopenia. Oxidative phosphorylation becomes impaired with aging, affecting muscle performance, and contributing to an age‐associated decline in mobility. However, it is unclear whether this deterioration is due to a reduced mitochondria population, decreased mitochondrial energetic efficiency, or a reduced capacity to dynamically transport oxygen and nutrients into the mitochondria, and addressing these questions is an active area of research. Further research in humans will require use of new "omics" technologies, progress in neuroimaging techniques that permit energy production assessment, and visualization of molecules critical for energetic metabolism, as well as proxy biomarkers of muscle perfusion.